Mit pewności prawnej, czyli dlaczego nieprecyzyjne standardy prawne mogą być lepsze dla kapitalizmu i liberalizmu - Raban, Ofer (Filozofia Publiczna i Edukacja Demokratyczna, 2013)
This article reviews key aspects of the theoretical debate on the distinction between bright-line rules framed in clear and determinate language and vague legal standards. It is generally believed that legal rules provide more certainty and predictability, while legal standards afford flexibility, accommodate equitable solutions, and allow for a more informed development of the law. Furthermore, the article seeks to refute the idea that bright-line rules are superior to vague standards in regard to certainty and predictability. In first section, the author articulates the claims that legal certainty and predictability are essential for both capitalism and liberalism, and that these systems of economic and political organization therefore require legal rules framed in clear and determinate language. Second section undertakes a critical valuation of that claim and argues that, oftentimes, the best-drafted clear and determinate rules would result in less certainty than alternative vague and indeterminate standards. Third section provides explanations why things are so, arguing that the law is but one of many normative systems; that competing economic, social, and moral standards are often couched in vague and indeterminate terms; and that many of these standards cannot be reduced to clear and determinate rules. As conclusion author pointed out on the extensive use of vague legal standards that with no doubt harbors dangers. Vague standards can easily mask arbitrariness, inconsistency, and injustice, and can also generate uncertainty. their proper use requires good faith, professionalism, and intelligence, and therefore depends on a high caliber legal profession.